Justisiablitias Hak Ekosob Melalui Mekanisme Individual Communication dalam Optional Protocol To The International Covenant On Economic, Social And Cultural Rights - Harison Citrawan (Jurnal HAM, 2014)
The individual communication mechanism enshrined under the Optional Protocol of the International Covenant on Economic, Social and Cultural Rights could be regarded as a form of state's commitment to make economic, social and cultural (ecosoc) rights justiciable. This paper attempts to depict several aspects of the working mechanism of individual communication exercised by the Ecosoc Rights Committee, including: admissibility of ratione personae, ratione temporis, and ratione materiae. Furthermore, analysis will be taken on the issue of whether such a mechanism could give an effective way to promote state's compliance on ecosoc rights fulfillment. In brief, this paper concludes several points: first, the Optional Protocol is to be regarded as a compromise between the nature of the rights and the duties ruled under the Covenant; second, the Ecosoc Rights Committee shall accommodate the need of adjudicative body in order to shift the traditional view of ecosoc rights; and third, there is a need of a comprehensive coordination and cooperation amongst both treaty based and charter based human rights institutions, not only on technical issues but also on the legal interpretation method.